Implementasi Media Pembelajaran Quizizz Terhadap Motivasi Belajar Peserta Didik Kelas XI Majamenen Perkantoran Dan Layanan Bisnis 3 SMK Negeri 1 Makassar: Implementation of Quizizz Learning Media on the Learning Motivation of Class XI Students of Office and Business Services 3 SMK Negeri 1 Makassar - Annisa AR, Nur; Darwis, Muhammad; Hajrah, St. (Jurnal Education, 2025)
This research aims to determine the implementation of the Quizizz learning media on the learning motivation of XI MPLB 3 students at SMK Negeri 1 Makassar. This Classroom Action Research (CAR) was conducted in two cycles. The subjects used in the study were 34 students, specifically from class XI MPLB 3 at SMK Negeri 1 Makassar. The data collection techniques used include observation, interviews, test observations, and documentation. The research results indicate a significant increase in student learning motivation, with Cycle I achieving a percentage of 66% and Cycle II reaching a percentage of 89%. The utilization and use of the Quizizz media not only enhanced students' learning motivation but also provided a new learning atmosphere. The indicators of success in this learning process are enthusiasm, motivation, involvement, and interest of the students. Thus, the significant increase in learning activity and the percentage of learning completeness from Cycle I to Cycle II proves that the Quizizz media is very effective as a support for success and enhances student motivation in the learning process, as well as creating a pleasant learning environment, especially for class XI MPLB 3 at SMK Negeri 1 Makassar.